The Medusa plot [compact disc, unabridged] - Korman, Gordon (39 clues. Cahills vs. Vespers, 2011)
Unable to return to their normal lives despite the end of the Clue hunt, new Madrigal leaders Amy and Dan anxiously prepare for a retaliatory strike by the Vespers, who kidnap a number of Cahill family members and demand that Amy and Dan steal a famous painting.